Lower mortality in an all-comers aortic stenosis population treated with TAVI in comparison to SAVR - Möllmann, Helge; Husser, Oliver; Blumenstein, Johannes; Liebetrau, Christoph; Dörr, Oliver; Kim, Won Keun; Nef, Holger; Tesche, Christian; Hamm, Christian W.; Elsässer, Albrecht; Achenbach, Stephan; Gaede, Luise (Clinical Research in Cardiology, 2019)
Background: Within the last years TAVI—especially transfemoral/transvascular TAVI—has proven to be a valuable therapeutic option for most patients suffering from AS. Here, we present the outcome of a complete dataset of all patients undergoing aortic valve replacement in Germany in 2018. Methods: The data of all aortic valve procedures performed in Germany in 2018 derive from the mandatory nationwide quality control program. Patients were stratified with a new version of the German Aortic valve score (AKL Score) divided in different risk stratification depending on the treatment with either a catheter based (TV-TAVI) or surgical (iSAVR) approach. In-hospital outcomes have been compared between the two approaches. Results: 19,317 transvascular (TV)–TAVI procedures were carried out. In contrast to this steady growth, the number of iSAVR andtransapical (TA) -TAVI procedures declined. In-hospital mortality after TV-TAVI (2.5%) was lower when compared to iSAVR (3.1%) as well as TA-TAVI (5.7%) in-hospital mortality after TV-TAVI was significantly lowest (Fig. 2) with an in-hospital mortality rate of 2.5%. TV-TAVI was the only approach with an observed vs. expected mortality ratio < 1 according to the used risk prediction model. Conclusion: TV-TAVI is more often performed and shows lower in-hospital mortality than iSAVR. TV-TAVI has replaced iSAVR as the gold-standard concerning in-hospital outcome in aortic stenosis management.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Mortality; Real-world; Registry; SAVR; TAVI; TAVR